MCDHF calculations of isotope shifts of even-parity fine-structure levels in neutral osmium. (December 2016) - Palmeri, P.; Quinet, P.; Bouazza, S.
Abstract: Ab initio multiconfiguration Dirac–Hartree–Fock (MCDHF) calculations have been carried out in order to determine the isotope shifts of all the fine-structure levels belonging to the even-parity configurations (5d+6s) 8 in neutral osmium, Os I. The theoretical predictions have been compared to laser spectroscopy measurements available in the literature showing a good agreement between theory and experiment. Abstract : Highlights: Ab initio fully relativistic MCDHF calculations of isotope shifts have been carried in neutral osmium. Relativistic normal mass shift, specific mass shift and field-shift factor electronic parameters are given for all known even-parity fine-structure levels belonging to the (5d+6s) 8 configurations. Comparison with experimental fine-structure level shifts shows a good agreement with our MCDHF predictions.